Restoring Greco-Roman Wrestling: Some Research and Philosophy. Issue 1 (2nd January 2016) - Dokmanac, Milorad; Curby, David G.; Petkovic, Momir
ABSTRACT: To make a contribution to the improvement of Greco-Roman wrestling, an effort was initiated to identify some causes for the decline in the technical level and scoring in Greco-Roman wrestling over the past 10 years. This analysis aimed to demonstrate how this preventative style of wrestling (holding fingers/wrists in a standing position) has a negative effect on the execution of self-focused, action-oriented wrestling techniques in the Greco-Roman style. To demonstrate the significant effect of holding fingers/wrists has on a wrestling match, an analysis of all medal matches of the 2015 World Wrestling Championships in Las Vegas, Nevada, was performed and quantified. The time parameters measured in each match were the total time of the match, total time in the standing position, and total time in par terre position. Wrestling in the standing position was further specified as time spent in normal contact, time without contact, and contact made by holding fingers/wrists. The amount of match time spent without contact, plus contact made by holding fingers/wrists is defined as obstructive/preventative wrestling . Wrestling in the standing position is the focus of this study and comprises 86% and 84% of the entire match time for the gold and bronze medal matches, respectively, with the balance being wrestled in the par terre position. From these data are derived the percent of time in standing spent in obstructive/preventative wrestling actions of grasping and locking of fingers and wrists, as well as time without contact. Means of 78% and 72% were found for gold and bronze medals, respectively. On the basis of these data, it is evident how much time is spent where there is no possibility to perform wrestling techniques, because the wrestlers are holding fingers or are completely separated without close contact in the wrestling standing position.